A Computerized Medical Standards System to Help Place Impaired Employees - Halpern, M. (Methods of Information in Medicine, 1996)
The paper describes a knowledge-distribution system that supports decisions on placement of impaired employees. The knowledge base consists of job profiles and medical profiles. The job profiles list tasks and the physical abilities they require. Twenty-one abilities describe the task demands. Active workers rated the exertion, frequency and importance of the physical ability required for each task. Thirty-nine work conditions were rated this way. Using identical scales, experts assessed the impact of impairments on the physical abilities of individuals and the tolerance of work conditions. The screening matches the job profile against the impairment profile. This process has been automated. The program lists tasks and work conditions that may compromise an impaired employee. This information can be used to accommodate employees, restrict duties or design a rehabilitation program. Also, the paper discusses the impact of the system on the operations of medical services within an organization.
Keywords: Job Analysis; Knowledge Bases; Decision-Support System; Occupational Health-Information Systems; Personnel Staffing and Scheduling Systems